Mutation of human Connexin43 amino acids S279/S282 increases protein stability upon treatment with epidermal growth factor - Schmitt, Melanie; Leykauf, Kerstin; Reinz, Eileen; Cheng, Hao; Alonso, Angel; Schenkel, Johannes (Cell biochemistry and biophysics, 2014)
Connexins are the structural units of gap junctions, structures allowing interchanging of information between the adjacent cells. Connexin43 (Cx43) is the most abundant gap junction protein. Cx43 can be degraded by lysosome- and proteasome-mediated processes upon internalisation of the entire structure. Only little is known about the role of phosphorylation during the gap junction degradation. In Cx43, a protein containing 14 amino acids susceptible to be phosphorylated, amino acids S279 and S282 are phosphorylated upon epidermal growth factor (EGF) treatment by erk1/2 MAP kinases. Here, we show that the wild-type Cx43 protein, as well as HeLa cells expressing the mutated Cx43 proteins S279A, S282A, and S279A/S282A, is mainly located at the plasma membrane. However, the protein stability is not altered in the isolated single mutants, whereas the double mutant S279A/S282A is strongly degradation impaired upon EGF treatment. This effect is not due to the decreased Cx43 internalisation, but seems to be related to a reduced ubiquitination.
Gesehen am 21.08.2020